Sizing and Study of the Energy Production of a Grid-Tied Photovoltaic System Using PVsyst Software - Muñoz, Yecid; Vargas, Orlando; Pinilla, Gustavo; Vásquez, Jairo (TECCIENCIA, 2017)
This paper describes analyses carried out on the sizing and simulation of a grid-tied photovoltaic system in Bucaramanga, Colombia with the virtual tool PVsyst. The simulation was primarily performed in order to understand the behavior of grid- tied photovoltaic installations at a specific location, while avoiding the oversizing or undersizing of the systems, thus projecting installations which better approximate real conditions. Theoretical calculations were performed conventionally in order to make comparisons of calculated data with simulation results. We highlight the good potential of the studied area, with 1882 kWh/m at optimal orientation, which would generate 1375 kWh/year for a 1 kW PV system, with a yield factor of 72.7%. Losses are disaggregated in this paper, including a study of the behavior associated with the tilt and orientation of the system. Such information on potential and performance is a valuable reference for any possible sizing of photovoltaic projects at similar latitude.